AIDING AND OPPOSING MIXED CONVECTION FROM AN ARRAY OF CIRCULAR CYLINDERS IN A SATURATED POROUS MEDIUM - A. Ahmed, Mohammed (Anbar Journal of Engineering Sciences, 2008)
Numerical solutions are presented for mixed convection from an array of circular cylinders embed in a saturated porous medium. The cylinders are at constant temperature(isothermal) and arranged in a staggered tube bank. Both aiding and opposing flow conditions are considered. Numerical calculations using finite difference method with body-fitted coordinates have covered a wide range of governing parameters(i.e.,10 ،ـ Re ،ـ 100, 0 ،ـ Gr ،ـ 400 and Pr = 0.7). Results are presented for streamline, isotherms and the local and the average Nusselt number at different values of the governing parameters. The present results are compared with previous theoretical results and show good agreement